EFFECTS OF ADDITION PROBIOTIC OF BACILLUS SP. BT3CL STRAIN OR BACILLUS SUBTILIS BR2CL STRAIN ON BROILER CHICKEN PRODUCTION AND CARCASS COMPOSITION - I K. Y., Kertiyasa; Mahardika, I G.; Mudita, I M. (Jurnal Peternakan Tropika, 2020)
This experiment as conducted to findproduction and composition of broiler chicken carcasses given probiotics Bacillus sp. BT 3 CL strain or Bacillus subtilis BR 2 CL strain . The research was carried out for 2 months in the Tajen Village, Penebel, Tabanan, Bali and continued with sample analysis at the Laboratory of Animal Nutrition and Food, Faculty of Animal Husbandry, Udayana University. The design used completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatment given was chicken without additional probiotic inoculants through drinking water (A), chickens were given additional probiotic bacteria inoculants Bacillus sp. BT 3 CL strain through drinking water (B), chickens given additional inoculant probiotic bacteria Bacillus subtilis BR 2 CL strain through drinking water (C) and chickens given additional probiotic bacterial inoculant combination Bacillus sp. BT 3 CL strain and Bacillus subtilis BR 2 CL strain through drinking water (D). The observed variables included cutting weight, carcass weight, carcass percentage, abdominal fat, carcass portion, and non carcass weight. The results showed that the administration of probiotic bacteria Bacillus sp.strains BT 3 CL or Bacillus subtilis strain BR 2 CL can produce carcass weight, breast weight, back percentage, upper thigh weight, lower thigh percentage and wing weight that are significantly higher (P<0.05) than chickens without additional probiotic inoculants (A) and with abdominal fat percentage which was markedly lower (P<0.05). Based on the results of this research concluded that the additionof probiotic bacteria Bacillus sp. BT 3 CL strain or Bacillus subtilis BR 2 CL strain can increase carcass weight, chest weight, upper thigh weight, lower thigh weight and broiler wing weight at 35 days and with lower abdominal fat percentage Keywords:Broiler, Bacillus sp. BT 3 CL, Bacillus subtilis BR 2 CL, Carcas’s Composition